PERANAN REKSADANA SYARIAH DALAM PENINGKATKAN INVESTASI DI INDONESIA - M RASYID RIDHA; BISMAR NASUTION; MAHMUL SIREGAR (Universitas Sumatera Utara, 2013)
Reksadana Moslem law represent the medium of mixture invesment joining share and obligation Moslem law in one product which dikelolah by Invesment Manager. Existence Reksadana prove that capital market not merely just just nob people monopolies. Pass the reksadana, petitborgeois under even also can enjoy the advantage from the company share. Meagrely investor money can enjoy the advantage from share and other invesment instrument, and will more and more opportunity to society to participate. Problem of this research How arrangement of reksadana of Moslem law in Indonesia, forms of agreement execution (akad) in invesment mechanism the reksadana Moslem law,and How protection punish to investor in invesment the reksadana Moslem law. Method used in this writing thesis is research method punish the normatif. With the data collecting in book study (library Reseach). Writer use bibliography research / library reseach. In this case research punish by bibliography research or referred with the research normative. Pursuant to research result obtained that Arrangement of reksadana Moslem law in Indonesia, arrangement concerning this reksadana in positive law, both for conventional and also which is pursuant to Principle Moslem law is same that is arranged in No. 8 Year about Capital Market technical regulation and in the form of Governmental Regulation, Decree Of The Minister For Finance, and regulation by Bapepam and regulation by Effect Exchange as Self Organitation Rgulatory (SRO). Forms of agreement Execution (akad) in invesment mechanism [pass/through] the reksadana Moslem law, mechanism of invesment reksadana in fact loo like with the sharing holder invesment. All investor and invesment manager